The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12931-018-0785-0
|View full text |Cite
|
Sign up to set email alerts
|

Pollution and respiratory disease: can diet or supplements help? A review

Abstract: Pollution is known to cause and exacerbate a number of chronic respiratory diseases. The World Health Organisation has placed air pollution as the world’s largest environmental health risk factor. There has been recent publicity about the role for diet and anti-oxidants in mitigating the effects of pollution, and this review assesses the evidence for alterations in diet, including vitamin supplementation in abrogating the effects of pollution on asthma and other chronic respiratory diseases. We found evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 240 publications
(187 reference statements)
0
71
2
2
Order By: Relevance
“…These are difficult to design due to the confounding factors of diet, obesity, comorbid illness, medication, and environmental exposure. 20 The idea that diet can help to reduce some of the effects of pollution on asthma has gained interest, and certain vitamins seem to attenuate the effects of air pollution on asthma. 8 1.22-2.48), suggesting that supplementation eliminated the risk's increase.…”
Section: Discussionmentioning
confidence: 99%
“…These are difficult to design due to the confounding factors of diet, obesity, comorbid illness, medication, and environmental exposure. 20 The idea that diet can help to reduce some of the effects of pollution on asthma has gained interest, and certain vitamins seem to attenuate the effects of air pollution on asthma. 8 1.22-2.48), suggesting that supplementation eliminated the risk's increase.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining a healthy diet, with plenty of fruit and vegetables, and keeping well hydrated is likely to help reduce short and long term health effects. There is suggestive evidence that antioxidant and fish oil supplementation and dietary intake may have a protective effect against air pollution exposure; however, more research is needed to support this.…”
Section: Health Protection Advice and Trade‐offsmentioning
confidence: 99%
“…However, the observation period of the studies was just a few weeks and none of the studies showed the effect on respiratory outcomes such as lung function and symptom. In one review article, omega-3 oil was shown to have an anti-inflammation effect and reduced asthma symptoms (39) However, these studies were observational study and no other studies of vitamin D or omega-3 oil as interventions are available. Therefore, we realized after brief literature search that a tool other than air filter could not be analyzed as an intervention for PM.…”
Section: Discussionmentioning
confidence: 99%